STUDY ON CLINICAL CHARACTERISTICS, RELATED FACTORS, RESULTS OF TREATMENT FACIAL TELANGIECTASIAS BY INTENSE PULSE LIGHT AT CAN THO HOSPITAL OF DERMATO - VENEREOLOGY IN 2020 - Phan, Viet Dung; Huynh, Van Ba (Cantho Journal of Medicine and Pharmacy, 2026)
Background: Facial telangiectasias involves many factors and is quite common in Dermatology hospitals. Objectives: This study aimed to describe clinical features, some factors related to facial telangiectasias and results of the treatment for facial telangiectasias by intense pulse light (IPL). Materials and methods: A cross sectional study was conducted on 37 patients having facial telangiectasias. Result: The rate of improvement in facial telangiectasias gradually increased during IPL treatment at 10.8% improvement at 0-25%, and 75.7% improvement at 2550% after the treatment, the survey showed that the level of satisfaction and very satisfied was quite high 91.8%, side effect (red skin) was only 5.4%, there was a relationship between the degree of facial telangiectasias and several factors. Conclusion: IPL is safe and highly effective in the treatment of facial telangiectasias.